Economic and monetary union in Europe and parallels with the Caribbean Region. - HALLET, A.J. Hughes (1996)
Reviews the argument for and progress toward monetary union in Europe. Focuses on how well the conditions for an optimal currency are met, and on the implications of adopting price stability as a target to the exclusion of growth and employment.